Odeurs, senteurs, parfums: signes et sens dans l’OEuvre poétique de Senghor - Nissim, Liana (Ponti/Ponts, 2021)
This essay is an analysis of the perfume motive in the Œuvre poétique by Léopold Sédar Senghor; it enquires after perfumes and smells, scents and fragrances: their numerous occurrences, their attributes and the figures of speech by which they are determined. The perfume motive turns out to be fully significant as it mightily expresses the deep unity of the sensible and the spiritual world mainly by the means of synesthesia, metaphors and symbols. Most importantly, in a visionary projection towards the future, it contributes creating the image of a new world, as Senghor used to dream of, and used to predict as possible in his poetry.